2002
DOI: 10.1002/ijc.10165
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐specific CD8+ T‐cell evolution in vivo: Response to peptide vaccination with Melan‐A/MART‐1

Abstract: Monitoring of CD8؉ T-cell responses in cancer patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 54 publications
1
34
1
Order By: Relevance
“…Because certain TCR Vh restrictions are often shared in patients with the same type of cancer, as determined by a sensitive spectratyping for the TCR Vh variable complementarity-determining region 3, it has been suggested that they represent expansions of TA-specific T cells (4 -7). In some cases, TA specificity of such TCR Vhrestricted T cells has been confirmed (24,25). A more recent analysis suggests that TCR Vh profiles in patients with cancer reflect expansions of clonal as well as non -clonal-reactive T cells (26), and that contractions of TCR Vh-restricted T cells are common.…”
Section: Discussionmentioning
confidence: 99%
“…Because certain TCR Vh restrictions are often shared in patients with the same type of cancer, as determined by a sensitive spectratyping for the TCR Vh variable complementarity-determining region 3, it has been suggested that they represent expansions of TA-specific T cells (4 -7). In some cases, TA specificity of such TCR Vhrestricted T cells has been confirmed (24,25). A more recent analysis suggests that TCR Vh profiles in patients with cancer reflect expansions of clonal as well as non -clonal-reactive T cells (26), and that contractions of TCR Vh-restricted T cells are common.…”
Section: Discussionmentioning
confidence: 99%
“…0, 2 and 16 weeks after initiation of therapy). Frozen PBMC were thawed for tetramer staining as described [11]. All MoAb were from Beckman/Coulter, Krefeld, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…CD4 + T cells were enriched from 3-5 · 10 7 PMBC using anti-CD8-coated immunomagnetic beads (Miltenyi, Bergisch Gladbach, Germany). The CD4 + , CD8-depleted PBMC population was incubated with the respective PE-labelled tetramer reagents (1 lg of tetramer/2 · 10 7 cells) for 2 h, washed once, and incubated for 15 min with an anti-PE-directed MoAb attached to immunomagnetic beads (Miltenyi, Bergisch Gladbach, Germany) as previously described [11]. Tetramer-sorted cells were exposed to autologous macrophages which had been infected either with M. tuberculosis or with Mycobacterium avium intracellulare as described in detail [19] for 72 h. The anti-DR-specific MoAb L243 was used to block MHC class II-restricted T-cell recognition of naturally processed and presented antigens, while the anti-MHC class I-specific MoAb w6/32 was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Although the immunogenicity of a number of TAA has been documented in clinical trials, their therapeutic potential has not been clearly assessed, with the exception of the Melan-A/MART-1 antigen. Indeed, the therapeutic usefulness of the Melan-A antigen in melanoma is supported by the analysis of several active [2,3] and passive [4][5][6][7][8][9] immunotherapy protocols targeting this antigen.…”
Section: Introductionmentioning
confidence: 99%